Functional conductive nanomaterials via polymerisation in nano-channels: PEDOT in a MOF. Issue 1 (5th September 2016) - Wang, Tiesheng; Farajollahi, Meisam; Henke, Sebastian; Zhu, Tongtong; Bajpe, Sneha R.; Sun, Shijing; Barnard, Jonathan S.; Lee, June Sang; Madden, John D. W.; Cheetham, Anthony K.; Smoukov, Stoyan K.
Abstract : Poly(3, 4-ethylenedioxythiophene) (PEDOT) is formed inside a metal–organic framework (MOF). MOF removal leads to sub-millimetre structures of the nanostructured conducting polymer. Abstract : Reactions inside the pores of metal–organic frameworks (MOFs) offer potential for controlling polymer structures with regularity to sub-nanometre scales. We report a wet-chemistry route to poly-3, 4-ethylenedioxythiophene (PEDOT)–MOF composites. After a two-step removal of the MOF template we obtain unique and stable macroscale structures of this conductive polymer with some nanoscale regularity.